GOLD CONCENTRATION IN LICHEN IN THE GOLD ORE FIELDS OF ALPINE TUNDRA LANDSCAPES - Taisayev T.T.; Konstantinova I.M. (My University, 1988)
We investigated the gold distribution in reindeer moss growing over gold fields and shows of the gold-quartz and gold-sulfide associations. The gold in the plant ash was determined by means of a spectroscope with a detection threshold of 0.5 ppb and by atomic adsorption. We find the lichens of alpine tundra rich in trace elements.